Enzymatic changes in granulosa cells of developing goat follicles - SANGHA, G K; MARWAHA, A (The Indian Journal of Animal Reproduction, 2023)
Enzyme activities were measured in granulosa cells from small (5mm) follicles of goat ovaries. Acid and alkaline phosphatases and lactate dehydrogenase increased in thegranulosa cells from small to large follicles. Levels of enzyme 3~ HSDH was very low in small and medium sizedfollicles and it increased dramatically in the granulosa cells oflarge follicles. The changes in enzyme systems havebeen correlated with the metabolism and the steroid biosynthesis in the granulosa cells of the maturing follicles.
Keywords: Granulosa cells; ovary; goat; ACP; AKP; LDH; 3bitaHSDH